2009
DOI: 10.1111/j.1600-0838.2009.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of static and dynamic stretching on leg flexor and extensor isokinetic strength in elite women athletes

Abstract: The aim of this study was to explore the effects of static and dynamic stretching of the leg flexors and extensors on concentric and eccentric peak torque (PT) and electromyography (EMG) amplitude of the leg extensors and flexors in women athletes. Ten elite women athletes completed the following intervention protocol in a randomized order on separate days: (a) non-stretching (control), (b) static stretching, and (c) dynamic stretching. Stretched muscles were the quadriceps and hamstring muscles. Before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
118
4
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(141 citation statements)
references
References 32 publications
(126 reference statements)
13
118
4
6
Order By: Relevance
“…The negative effects of SS on muscle force and muscle force production has previously been reported (1,3,4,6,(10)(11)(12)(13)(14)(15)(16)28). Our study showed that SS at 60 and 300 degrees per second did not affect the PT in the stretched extremity.…”
Section: Discussionsupporting
confidence: 70%
“…The negative effects of SS on muscle force and muscle force production has previously been reported (1,3,4,6,(10)(11)(12)(13)(14)(15)(16)28). Our study showed that SS at 60 and 300 degrees per second did not affect the PT in the stretched extremity.…”
Section: Discussionsupporting
confidence: 70%
“…Among the various ways to stretch are: prolonged relaxation, dynamic or ballistic stretching and passive (static) stretching. Passive stretching is the safest and most commonly used form of stretching [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The acute effect of passive stretching allows the excitability reduction of alpha motor neuron for low-speed, creating better adaptations of muscle and connective tissue, and promoting their mechanical properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Athletes use many different types of stretching that are usually based only on their personal preference, but no optimal type or amount of stretching exercises has been identified [6]. The intended purposes of stretching before an athletic event are to insure that the individual has sufficient flexibility of joints to perform the athletic activity optimally and to decrease muscle stiffness or increase muscle compliance, thereby theoretically decreasing injury risk [9]. In addition to aerobic warm-up, different kinds of stretching exercises are widely used, including ballistic, proprioceptive neuromuscular facilitation, static and dynamic stretching [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…The intended purposes of stretching before an athletic event are to insure that the individual has sufficient flexibility of joints to perform the athletic activity optimally and to decrease muscle stiffness or increase muscle compliance, thereby theoretically decreasing injury risk [9]. In addition to aerobic warm-up, different kinds of stretching exercises are widely used, including ballistic, proprioceptive neuromuscular facilitation, static and dynamic stretching [6,9]. To find out the optimal warm-up program and to select exercises which improve the contraction speed and power of muscle-tendon unit, and help to prevent injuries simultaneously are actual in sports practise.…”
Section: Introductionmentioning
confidence: 99%